Hole Defects Affect the Dynamic Fracture Behavior of Nearby Running Cracks - R. S. Yang; C. X. Ding; L. Y. Yang; P. Xu; C. Chen (Shock and Vibration)
Effects of defects on the dynamic fracture behavior of engineering materials cannot be neglected. Using the experimental system of digital laser dynamic caustics, the effects of defects on the dynamic fracture behavior of nearby running cracks are studied. When running cracks propagate near to defects, the crack path deflects toward the defect; the degree of deflection is greater for larger defect diameters. When the running crack propagates away from the defect, the degree of deflection gradually reduces and the original crack path is restored. The intersection between the caustic spot and the defect is the direct cause of the running crack deflection; the intersection area determines the degree of deflection. In addition, the defect locally inhibits the dynamic stress intensity factor of running cracks when they propagate toward the defect and locally promotes the dynamic stress intensity factor of running cracks when they propagate away from the defect.